2011
DOI: 10.1002/jctb.2593
|View full text |Cite
|
Sign up to set email alerts
|

Co‐culture of Penicillium chrysogenum and Saccharomyces cerevisiae leading to the immobilization of yeast

Abstract: BACKGROUND: Under appropriate conditions, Saccharomyces cerevisiae and Penicillium chrysogenum were found to coimmobilize spontaneously with no need for external support or chemical binder. The main aims were to examine the interaction between yeast cells and fungal hyphae by electron microscopy and the death of the filamentous fungus because of direct contact between both microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…In addition, the use of immobilised yeast cells facilitate the retreat of yeasts. According to Peinado et al, 2006) a special procedure to immobilise two osmotolerant yeast strains (X4 and X5) has been recently carried out (García-Martínez, Peinado, Moreno, García-García, & Mauricio, 2011;García Martinez, Puig-Pujol, Peinado, Moreno, & Mauricio, 2012) with show some advantages in relation to the use of free yeast (i) the ability to withdraw the yeast cells when desired, (ii) reuse them in other fermentation runs, where the process will start earlier and last shorter thanks to the activated state of the yeasts, as well as (iii) a reduced risk of contamination and decreased costs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of immobilised yeast cells facilitate the retreat of yeasts. According to Peinado et al, 2006) a special procedure to immobilise two osmotolerant yeast strains (X4 and X5) has been recently carried out (García-Martínez, Peinado, Moreno, García-García, & Mauricio, 2011;García Martinez, Puig-Pujol, Peinado, Moreno, & Mauricio, 2012) with show some advantages in relation to the use of free yeast (i) the ability to withdraw the yeast cells when desired, (ii) reuse them in other fermentation runs, where the process will start earlier and last shorter thanks to the activated state of the yeasts, as well as (iii) a reduced risk of contamination and decreased costs.…”
Section: Introductionmentioning
confidence: 99%
“…The natural formation of spherical bodies from the adhesion process in aqueous solutions enables study of cross-species attachment in a more complex, yet controllable, setting. García-Martínez et al (2011) investigated the interaction of Saccharomyces cerevisiae yeast with Penicillium chrysogenum hyphae within the biocapsules using electron microscopy and confirmed that the yeast cells were directly attached to the surface of ff hyphae. In fermentative media, the ff lose viability and remain as a highly inert form of support for the yeast.…”
Section: Introductionmentioning
confidence: 93%
“…P. chrysogenum strain H3 was isolated by the same research group and identified by the Spanish Collection of Standard Cultures (CECT). This strain was selected in terms of the ease with which it forms strong biocapsules that are highly resistant to fermentation conditions (García-Martínez et al, 2011).…”
Section: Microorganisms and Biocapsules Productionmentioning
confidence: 99%
“…Production of biocapsules was carried out according to García-Martínez et al (2011), under special conditions in a formation medium consisting of yeast nitrogen base without amino acids (YNB, Difco, Becton Dickinson and Company, Sparks, MD) containing a 5 g/L concentration of gluconic acid (SigmaeAldrich, St. Louis, MO) as carbon source. The medium was buffered at pH 7 with sodium and potassium phosphate.…”
Section: Microorganisms and Biocapsules Productionmentioning
confidence: 99%
See 1 more Smart Citation